2019
DOI: 10.1108/itp-09-2018-0410
|View full text |Cite
|
Sign up to set email alerts
|

Role of empowerment and sense of community on online social health support group

Abstract: Purpose Drawing on the taxonomy of patient empowerment and a sense of community (SoC), the purpose of this paper is to analyze the factors that impact the intention of the individual to continue using online social health support community for their chronic disease management. Design/methodology/approach A survey design was used to collect the data from multiple online social health support groups related to chronic disease management. The survey yielded a total of 246 usable responses. Findings The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 74 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…Empowering patients for independent disease management also has a positive effect on the patient’s psychological state through patient self-confidence [ 4 , 8 , 9 ], positive self-perception [ 9 ], and self-esteem [ 3 ]. Research also highlights the results of patient empowerment via the social dimension, as empowering the patient to act independently has a positive effect on his interpersonal relationships with relatives, healthcare professionals [ 5 , 10 , 11 , 12 , 13 ], and communities of patients with the same disease [ 32 ]. Finally, the empowerment of a patient with chronic illness manifests itself in their behavior through conscious internal control of behavior self-efficacy, which allows them to make rational decisions for self-management of chronic illness and is a key precondition for health behaviors [ 9 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowering patients for independent disease management also has a positive effect on the patient’s psychological state through patient self-confidence [ 4 , 8 , 9 ], positive self-perception [ 9 ], and self-esteem [ 3 ]. Research also highlights the results of patient empowerment via the social dimension, as empowering the patient to act independently has a positive effect on his interpersonal relationships with relatives, healthcare professionals [ 5 , 10 , 11 , 12 , 13 ], and communities of patients with the same disease [ 32 ]. Finally, the empowerment of a patient with chronic illness manifests itself in their behavior through conscious internal control of behavior self-efficacy, which allows them to make rational decisions for self-management of chronic illness and is a key precondition for health behaviors [ 9 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stages of the action cycle can occur sequentially or overlap, and the cycle of knowledge formation can influence the action cycle at any stage. The elements of the action cycle focus on deliberately bringing about change in healthcare systems and groups [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The above behaviors are different types of user behaviors, contributing behaviors, social support behaviors, and patients' doctor selection behavior, etc.. Yang and Zhu (2020) believe that based on the information ecosystem, online health communities mainly include information people, information, information environment, and information technology. Research by Sharma and Khadka (2019) showed that information support is the main type of support people seek from online social health support communities. Realizing the complexities of information behavior and the needs in the online health community, it makes us to ask more and more questions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since Malaysia is a polychromic culture whereby multitasking is given priority (Tan and Ooi, 2018), PM was added. Further, a system has a higher propensity to be adopted if the particular technology is compatible with the user's work styles, experiences and lifestyles as it enhances the feeling of belonging, identity and familiarity (Sharma and Khadka, 2019). Therefore, perceived compatibility (PC) was integrated.…”
Section: Theoretical Backgroundmentioning
confidence: 99%